(untitled) (Journal of the College of Basic Education, 2022)
The idea of ​​research is designing automatic electro-acoustic systems to achieve a better intelligibility of speech in the mosques, through the study of a group of large mosques and calculate the number of worshipers (or the number of the rows of worshipers) in each period of time (each prayer) Per day and repeat this process for a year, but on different days determined by the climatic conditions, opening hours, holidays and religious occasions. and each of the mosques that have been selected according to these data in addition to the identification of architectural forms and the common finishing materials in mosques are proposed loudspeakers distribution systems of the mosques that are divided in the form of groups, each group covering a specific area appropriate for the regularity of the congregation during the prayer in the form of straight rows accredited this regularity of worshipers in prayer for the operation of each of these groups as needed to ensure that you get the best intelligibility of speak, as it is known that the sound absorption increases with the increasing of worshipers number, and how that will be effects on reverberation time of the voice (RT), so we can use movement sensors or cameras to count the number of worshipers or the number of rows of worshipers, or by determining the area filled with worshipers. Then by the using of an electronic board or by a computer we can automatically operate the speakers which cover that area and with the increasing of worshipers number the other groups of speakers will be operated one after the other as needed depending on the number of worshipers which ensure the maintenance of heterogeneous distribution of acoustic energy and achieve the best intelligibility of speech.